Penerapan Metode Bercerita Dalam Pengembangan Bahasa Anak Usia Dini 5-6 Tahun - Setiawati, Nanik; Putra, Darma; Zukhairina, Zukhairina (Al-Miskawaih: Journal of Science Education, 2023)
This study aims to determine the extent to which the storytelling method is applied in children's language development in group B aged 5-6 years at Diniyyah Al-Azhar Kindergarten, Jambi City. This research is a descriptive qualitative research with an ethnographic approach. Data collection techniques using observation, interviews and documentation. The analysis technique used is data reduction, data presentation and conclusion. The research findings show that the application of the storytelling method in the development of children's language at the Diniyyah Al-Azhar Kindergarten, Jambi City has been well implemented. The results of achievement according to children's language development are measured from indicators of achievement of child development in the scope of children's language development aged 5-6 years. The development indicators include; children can understand language by repeating commands simultaneously, repeating more complex sentences, and understanding the rules of a game. On the other hand, children are also able to answer more complex questions, increase vocabulary, and compose sentences with complete structures. Penelitian ini bertujuan untuk mengetahui sejauh mana penerapan metode bercerita dalam perkembangan bahasa anak di kelompok B usia 5-6 tahun Taman Kanak-Kanak Diniyyah Al-Azhar Kota Jambi. Penelitian  ini merupakan penelitian kualitatif deskriptif dengan pendekatan etnografi. Teknik pengumpulan data menggunakan observasi, wawancara dan dokumentasi. Teknik analisis yang digunakan adalah reduksi data, penyajian data dan penarikan kesimpulan. Temuan penelitian menunjukkan bahwa penerapan metode bercerita dalam pengembangan bahasa anak pada Taman Kanak-Kanak Diniyyah Al-Azhar Kota Jambi sudah terlaksana dengan baik. Hasil pencapaian sesuai perkembangan bahasa anak yaitu diukur dari indikator pencapaian perkembangan anak lingkup perkembangan bahasa anak usia 5-6 tahun. Indikator  perkembangan itu antara lain; anak dapat memahami bahasa dengan mengulang perintah secara bersamaan, mengulang kalimat yang lebih kompleks, dan memahami aturan dalam suatu permainan. Di sisi lain anak-anak juga mampu menjawab pertanyaan yang lebih kompleks, perbendaharaan kata bertambah, serta menyusun kalimat dengan struktur lengkap.